Silicon carbide growth: C/Si ratio evaluation and modeling - Pons, Michel; Nishizawa, Shin-Ichi; Wellmann, Peter; Blanquet, E.; Chaussende, D.; Dedulle, J.M.; Madar, R. (Materials Science Forum, 2009)
Modeling and simulation of the SiC growth processes, Physical Vapor Transport (PVT), Chemical Vapor Deposition (CVD) and hybrid techniques, are sufficiently mature to be used as a training tool for engineers as well as a growth machine design tool, e.g. when building new process equipment or up-scaling old ones. It is possible (i) to simulate accurately temperature and deposition distributions, as well as doping (ii) to quantify the limiting phenomena, (iii) to understand the important role of different precursors in CVD and hydrogen additions in PVT. The first conclusion of this paper is the importance of the "effective" C/Si ratio during CVD epitaxy in hot-wall reactors and its capability to explain the doping concentrations. The second conclusion is the influence of the C/Si ratio in alternative bulk growth technique involving gas additions. Preliminary results show that fine tuning of H2 or precursor additions allow a better control of concentrations of residual and intentional dopin
Keywords: Modeling; Simulation; Growth; Mass transport; C/Si ratio